KULTURA A GLOBALIZACJA: PROBLEMY ZASADNICZE - Krasiwski, Orest (Studia Europaea Gnesnensia, 2018)
The article analyzes the influence of globalization on the cultural processes of society, exploring the significance of global culture for self-identification and selfdetermination, as well as its impact on local national culture. The author investigation the reasons behind glocalisation, also showing the consequences of the spread of mass culture, the transition of the western way of life, values and ideals of the consumption society.